Training the Future Leaders in Personalized Medicine - Mason-Suares, Heather (J Pers Med, 2016)
The era of personalized medicine has arrived, and with it a need for leaders in this discipline. This generation of trainees requires a cadre of new skill sets to lead the implementation of personalized medicine into mainstream healthcare. Traditional training programs no longer provide trainees with all the skills they will need to optimize implementation of this revolution now underway in medicine. Today’s trainees must manage clinical teams, act as clinical and molecular diagnostic consultants, train other healthcare professionals, teach future generations, and be knowledgeable about clinical trials to facilitate genomic-based therapies. To prepare trainees for the transition to junior faculty positions, contemporary genomic training programs must emphasize the development of these management, teaching, and clinical skills.